Auswirkung von 7 und 3 Wochen Höhentraining innerhalb einer 5-Montate-Trainingsperiode auf die Hämoglobinmasse und die VO2max bei Nationalmannschaftskilangläufern - Wehrlin, J.; Hallén, J.; German, C.; Villiger, B.; Marti, B. (ARGE Alpinmedizin, 2007)
This work will controbute to the actual debate inot if, but why, there are improvements in sea-level performance after LHTL. The aim of the study was to study the effects of several altitude training periods over a five-month pre-season training phase on erythropoiesis (hemoglobin mass, red cell volume, plasma volume and blood volume) and VO2max in national team cross country skiers. The conclusions are: Conclusions - Hemoglobin mass increased by 4-5% with a three-week combined LHTH and LHTL altitude training period (400h at ~2500m) (No change in hemoglobin mass with a one-week LHTH altitude training period; 150h at ~2500m) - Hemoglobin mass can increase further with a supplementary three-week altitude training camp (up to + 8%) - Red cell volume can decrease over a five-month training period combined with one-week altitude training periods => There is no reduction in red cell volume if the amount of altitude training is increased (3 + 1 + 3) - A five-month training period combined with altitude training can decrease in mean corpuscular volume of the erythrocytes. We can only speculate about the reasons for this phenomenon. More research is needed. - We recommend to measure hemoglobin mass and red cell volume with the CO-rebreathing technique - A five-month training period combined with 3 + 1 + 3 weeks altitude training increase VO2max while no change was seen with 1 + 1 + 1 week altitude training. = > Effect on the aerob pathway of performance? => However, only the 1 + 1 + 1 group increased time to exhaustion (similar but only tendency in the 3 + 1 + 3 group)